Effect of Cultural Distinctiveness and Perception of Digital Advertising Appeals on Online Purchase Intention of Clothing Brands: Moderation of Gender Egalitarianism - Syed Hassan Raza; Umer Zaman (Information, 2021)
Digital advertising has been frequently used for the promotion of e-commerce among individuals. However, little is known about the function of cultural factors that can outline the effectiveness of digital advertising practices to alter attitude and consumer behavior toward clothing brands. This research examines how norm-congruent attitudes toward digital advertising (hereafter ADA) may operate as a process variable that mediates the relationship between perception about digital advertising (hereafter PDA) and online purchase intention of fashion brands (hereafter OPI). We propose a gender egalitarianism (hereafter GE)-moderated mediation model whereby ADA mediates the relationships between PDA and OPI in two culturally diverse nations: Malaysia and Pakistan. The model was tested by using 2 (GE appeal: present vs. absent) × 2 (nation: Pakistan vs. Malaysia) × 2 (no exposure to ads/exposure to ads) experimental design with data obtained from a sample of 260. Findings show that there is a significant difference in the relationship between PDA and OPI that is mediated by the attitude in both nations. However, the mediation implication of the attitude is significantly dependent on the interaction of the GE. In this way, the study provides some practical recommendations for the marketers by highlighting the salient advertising features that may be more useful in both nations.